Antibody-Mediated Therapy against HIV/AIDS: Where Are We Standing Now?. (3rd June 2018) - Awi, Noel Jacques; Teow, Sin-Yeang
Abstract : Acquired immunodeficiency syndrome (AIDS) cases are on the rise globally. To date, there is still no effective measure to eradicate the causative agent, human immunodeficiency virus (HIV). Highly active antiretroviral therapy (HAART) is being used in HIV/AIDS management, but it results in long-term medication and has major drawbacks such as multiple side effects, high cost, and increasing the generation rate of escape mutants. In addition, HAART does not control HIV-related complications, and hence more medications and further management are required. With this, other alternatives are urgently needed. In the past, small-molecule inhibitors have shown potent antiviral effects, and some of them are now being evaluated in clinical trials. The challenges in developing these small molecules for clinical use include the off-target effect, poor stability, and low bioavailability. On the other hand, antibody-mediated therapy has emerged as an important therapeutic modality for anti-HIV therapeutics development. Many antiviral antibodies, namely, broad neutralizing antibodies (bnAbs) against multiple strains of HIV, have shown promising effects in vitro and in animal studies; further studies are ongoing in clinical trials to evaluate their uses in clinical applications. This short review aims to discuss the current development of therapeutic antibodies against HIV and the challenges in adopting them for clinical use.